Studying the characteristics of heavy rainfall in the central coastal provinces of Vietnam (Quang Binh case study) - Nguyen Van Thang; Vu Van Thang; Tran Dinh Trong; Jerome Faucet (Vietnam Journal of Science, Technology and Engineering, 2022)
This paper explores the maximum amount of rainfall in the Central coastal provinces of Vietnam (Quang Binh case study) for return periods of 5 years, 10 years, 20 years, 50 years, and 100 years, which correspond to frequencies of 20%, 10%, 5%, 2%, and 1%, respectively. The results show that at a frequency of 20%, the maximum intensity of rain during a heavy rain spell can range from 636.6 to 696.0 mm, while the maximum one-day amount received was over 300 mm, which can occur many times in 5 years. At a frequency of 1%, the intensity of rain during a heavy rain spell can range from 1,197.9 to 1,268.3 mm, while the maximum one-day amount ranged from 487.4 to 521.9 mm. However, such values are very rare over the course of 100 years. In addition, in terms of annual rainfall, the spatial distribution of heavy rainfall in coastal areas was significantly smaller than that in mountainous areas. The highest one-day and five-day rainfall have the same pattern of spatial distribution as annual rainfall.